Konflik Antara Kewajiban Esg dan Perlindungan Investor dalam Investor-State Dispute Settlement (ISDS) - Heryanty Hasan (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This article aims to analyze the extent to which the Investor-State Dispute Settlement (ISDS) regime is able to accommodate Environmental, Social, and Governance (ESG) obligations without eroding state regulatory space in protecting the public interest. This research uses normative legal methods with a conceptual and comparative approach, combined with case study analysis of international investment arbitration awards. The analysis focuses on the tension between investor protection clauses, particularly fair and equitable treatment and indirect expropriation, and state policies in the environmental, social, and governance fields. The results show that the conventional ISDS framework still tends to position investor rights as legally enforceable claims, while state ESG obligations are generally soft law and unjusticiable. Developing reforms, such as the European Union's Investment Court System, the revision of the Bilateral Investment Treaty model with public policy exception clauses, and the multilateral reform agenda of UNCITRAL Working Group III, have not fully addressed this structural asymmetry. This research concludes that the partial insertion of ESG clauses in investment treaties is inadequate, necessitating a redesign of the international investment legal regime that balances legal certainty for investors with protection of the public interest and sustainability.